Assessment of Referral System Quality from Clients’ Perspectives at Outpatient Consultancy Clinics in Al-Hilla City Hospitals - Mahdi Hamzah Manthoor Al-Taee1 , Mahasin Talib Al-Harbawi2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Aim: The aim of the study is to assess the referral system quality from clients’ perspectives at outpatient consultancy clinics in al-Hilla city hospitals. Subjects and Methods: A descriptive analytic study design was carried out at outpatient consultancy clinics of Al- Hilla city hospital (Al-Hilla and Al-Imam Al-Sadiq general teaching hospital) from March 14 th to December 12 th 2019. Non – probability (purposive) sample of 200 clients who were coming to the Outpatient Consultancy Clinics were selected. Data is collected through used of an assessment tools and interview technique with (19) items of questionnaire. Reliability of instrument was determined through the use of Alpha Cronbach approach and the instrument validity was determined through a panel of experts. The analysis of the data was used descriptive statistics frequencies, percentages, mean, mean of score, cut off point, Chi square. In order to assess the referral system quality from clients’ perspectives. Results: The findings of the present study reveal that overall assessment of the referral system quality is poor, grand mean of referral system services from clients’ perspectives are fair, majority reason for referring is lack of specialty(51%), and finally; medical diseases unit is most referred clients to it(24%). . Conclusion: The study concluded that poor referral system quality for clients at outpatient consultancy clinics in Al-Hilla city hospitals.